Developing of an Interactive Web-based Learning Medias on Pediatric Nursing Skills for Student Nurses - ศรีบุณยวัฒน ณัฏฐณิชา; นิยมค้า ศรีมนา; มีสุขโข จุฑารัตน์; สุขเลิศตระกูล ฐิติมา; อารีย์ พัชราภรณ์; สารากร จันท์พิมพ์ (Nursing Journal CMU, 2019)
To encourage understanding, retention, and satisfaction with instruction, the multimedia web-based learning is recognized as one of the alternative teaching techniques to supplement the traditional classroom style. This development research study aimed to develop and to evaluate the efficiency of an interactive web-based learning medias on pediatric nursing skills for student nurses, composed of tub-bath, suction, feeding, and oxygen. Fifty nurse students were chosen by simple random sampling. The research instruments, which were developed by the researcher, included 1) demographic data profile, 2) pre-and post knowledge assessments on pediatric nursing skills and satisfaction questionnaires. These pre-and post knowledge on four skills of pediatric nursing questionnaires were validated by the expert panel and the scale content validity index of scale was .81, .88, .89, and 80 respectively. The stability reliability by Kuder-Richardison formula 21(KR-21) values of the scale was acceptable at .91, .88, .86, and 93, respectively. And 3) an interactive web-based learning medias a newly developed by researcher. The efficiency of an interactive web-based learning media was tested through individual and small group use, and by field test. Data was analyzed using description statistic and paired t-test. The results showed that interactive web-based efficiency was 80.6/81.3indicating acceptable criterion (80/80). It can be used as a way to broaden the knowledge of pediatric nursing students and thus improve their practices of pediatric nursing practice.